Organic minerals with different chemical characteristics in diets for Hy-Line White laying hens: performance, biometry of digestive organs, and bone quality - Maria Rogervânia Silva de Farias; Silvana Cavalcante Bastos-Leite; Constância Pontes Moura; Adailton Camêlo Costa; Cláudia Goulart de Abreu; Thaís Lucas de Sena (Revista Brasileira de Zootecnia, 2019)
ABSTRACT Two trials were carried out to evaluate the effect of groups of organic minerals with different chemical characteristics on the performance, egg quality, biometry of digestive organs, and bone quality of laying hens in the first and second laying cycles. In the first cycle, 180 layers at 72 weeks were used in a completely randomized design (CRD) with four treatments and five replicates with nine birds each. In the second cycle, 216 layers at 94 weeks of age were used in a CRD with four treatments and six replicates with nine birds each. Birds were fed the following diets: treatment 1 - basal diet (inorganic minerals); treatment 2 - basal diet + amino acid chelated minerals (Cu, Fe, Mn, and Zn) + selenium yeast; treatment 3 - basal diet + mineral-amino acid complex (Mn, Zn, and Cu); and treatment 4 - basal diet + metal chelate (Mn, Zn, and Cu) + methionine hydroxy analogue. The following performance variables were evaluated: feed intake (g/bird/day), egg production (%), egg weight (g), egg mass (g/bird/day), conversion per mass (kg/kg), and conversion per dozen eggs (kg/dz). In the egg, the percentages of albumen, yolk, and shell; eggshell thickness (mm); and specific gravity (g/cm3) were determined. The relative weights (%) of the proventriculus, gizzard, liver, pancreas, and intestines were also measured. Lastly, in the tibiae, the weight (g), length (mm), resistance (kgf/cm2), deformity (mm), Seedor index (mg/mm), and mineral matter content (g/kg) were measured. The variables were not influenced by the groups of organic minerals used. Groups of organic minerals with different chemical characteristics can be used in layer diets without affecting their performance, egg quality, digestive organs, or bone quality.